A retrospective analysis of normal saline and lactated ringers as resuscitation fluid in sepsis - Isha, Shahin; Satashia, Parthkumar H.; Yarrarapu, Siva Naga S.; Govero, Austin B.; Harrison, Michael F.; Baig, Hassan Z.; Guru, Pramod; Bhattacharyya, Anirban; Ball, Colleen T.; Caples, Sean M.; Grek, Ami A.; Vizzini, Michael R.; et al. (Frontiers in Medicine, 2023)
Background: The Surviving Sepsis Campaign suggested preferential resuscitation with balanced crystalloids, such as Lactated Ringer’s (LR), although the level of recommendation was weak, and the quality of evidence was low. Past studies reported an association of unbalanced solutions, such as normal saline (NS), with increased AKI risks, metabolic acidosis, and prolonged ICU stay, although some of the findings are conflicting. We have compared the outcomes with the preferential use of normal saline vs. ringer’s lactate in a cohort of sepsis patients. Method: We performed a retrospective cohort analysis of patients visiting the ED of 19 different Mayo Clinic sites between August 2018 to November 2020 with sepsis and receiving at least 30 mL/kg fluid in the first 6 hours. Patients were divided into two cohorts based on the type of resuscitation fluid (LR vs. NS) and propensity-matching was done based on clinical characteristics as well as fluid amount (with 5 ml/kg). Single variable logistic regression (categorical outcomes) and Cox proportional hazards regression models were used to compare the primary and secondary outcomes between the 2 groups. Results: Out of 2022 patients meeting our inclusion criteria; 1428 (70.6%) received NS, and 594 (29.4%) received LR as the predominant fluid (>30 mL/kg). Patients receiving predominantly NS were more likely to be male and older in age. The LR cohort had a higher BMI, lactate level and incidence of septic shock. Propensity-matched analysis did not show a difference in 30-day and in-hospital mortality rate, mechanical ventilation, oxygen therapy, or CRRT requirement. We did observe longer hospital LOS in the LR group (median 5 vs. 4 days, p=0.047 and higher requirement for ICU post-admission (OR: 0.70; 95% CI: 0.51-0.96; p=0.026) in the NS group. However, these did not remain statistically significant after adjustment for multiple testing. Conclusion: In our matched cohort, we did not show any statistically significant difference in mortality rates, hospital LOS, ICU admission after diagnosis, mechanical ventilation, oxygen therapy and RRT between sepsis patients receiving lactated ringers and normal saline as predominant resuscitation fluid. Further large-scale prospective studies are needed to solidify the current guidelines on the use of balanced crystalloids.